2016
DOI: 10.1007/s00208-016-1393-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonexistence of solutions to parabolic differential inequalities with a potential on Riemannian manifolds

Abstract: Abstract. We are concerned with nonexistence results of nonnegative weak solutions for a class of quasilinear parabolic problems with a potential on complete noncompact Riemannian manifolds. In particular, we highlight the interplay between the geometry of the underlying manifold, the power nonlinearity and the behavior of the potential at infinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…for p ≤ 1 + 2/n), in accordance with [21] and [22]. Moreover, we underline that previous similar Liouville-type theorems (see for instance [14] and references therein) require the nonnegativity of the solutions, while here we just assume their boundedness from below.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…for p ≤ 1 + 2/n), in accordance with [21] and [22]. Moreover, we underline that previous similar Liouville-type theorems (see for instance [14] and references therein) require the nonnegativity of the solutions, while here we just assume their boundedness from below.…”
Section: Introductionsupporting
confidence: 69%
“…Subsequently, several generalizations to more quasilinear parabolic operators (p-Laplacian or porous medium-type, for instance) have been developed, see [8,9,16,18] and references therein. At the same time, extensions have been carried out also in the context of Riemannian manifolds: in the papers [21,22] (see also [14] and references therein), Zhang proved the same result of Fujita for the equation u t = ∆u + |u| p V on a Riemannian manifold (M, g), under some geometrical assumptions and growth conditions on the weight V in the case this latter is time-independent. In this work we remove the positivity hypothesis by such conclusion of nonexistence of nonzero solutions (equivalently, of triviality), assuming only a bound from below that, as we will see, implies the positivity of the solutions, moreover, we extend the work of Zhang by considering weights V which can depend also on time.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, quasilinear degenerate (or singular) parabolic equations of the type of (1.1) on Riemannian manifolds have attracted a lot of interest: with no claim to completeness, we quote e.g. [26,19,20,22,23,5,14,25,6,9,13,7,8] (see also the significant papers [15,10,12,11,16] in the purely parabolic case). In particular, in [7] problem (1.1) has thoroughly been studied under the assumption In [7,Theorem 2.2] it is shown that if the initial datum complies with the growth estimate |u 0 (x)| ≤ C (1 + ρ(x)) σ m−1 for a.e.…”
Section: Introductionmentioning
confidence: 99%
“…Subtituding above into (15) , we have But u 0 ≥ 0 is not identically zero, by Maximum principle, we know that u is positive almost everywhere, which leads a contradiction, and then there's no nonnegative solution to problem (1).…”
Section: Proof Of Theorem 14mentioning
confidence: 99%
“…Recently, this idea was used and developed for solutions to both elliptic equations (see, e.g. [11,12,18,19]) and parabolic equations (see [15]). Particularly in [15], Mastrolia, Monticelli and Punzo proved that if…”
Section: Introductionmentioning
confidence: 99%